2000
DOI: 10.1007/s001340000589
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided percutaneous dilatational tracheostomy: a safe method to avoid cranial misplacement of the tracheostomy tube

Abstract: The aim of this investigation was to evaluate the role of ultrasonography in avoiding cranial misplacement of the tracheostomy tube and tracheal ring fractures during percutaneous dilatational tracheostomy (PDT). The tracheas of 26 consecutive ICU patients who had undergone PDT but who later died were removed en bloc at autopsy. The tracheas were opened along the membranous portion and the condition of tracheal rings and the site of tracheostomy macroscopically evaluated. The patients were divided in two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(37 citation statements)
references
References 4 publications
0
37
0
Order By: Relevance
“…Ultrasonography allows optimal selection of the intercartilaginous space for the tracheostomy tube placement, avoiding eventual cranial misplacement. 5,8 Moreover, it has been recently demonstrated that ultrasound-guided PDT, in contrast to endoscopic guidance, is not accompanied by significant hypercarbia or elevation of intracranial pressure, conditions that could be detrimental in neurosurgical patients. 11,12 Endotracheal tube cuff puncture, or even puncture of the Murphy eye, are well known and reported complications of PDT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrasonography allows optimal selection of the intercartilaginous space for the tracheostomy tube placement, avoiding eventual cranial misplacement. 5,8 Moreover, it has been recently demonstrated that ultrasound-guided PDT, in contrast to endoscopic guidance, is not accompanied by significant hypercarbia or elevation of intracranial pressure, conditions that could be detrimental in neurosurgical patients. 11,12 Endotracheal tube cuff puncture, or even puncture of the Murphy eye, are well known and reported complications of PDT.…”
Section: Discussionmentioning
confidence: 99%
“…1-3 However, the "blind" technique is burdened with potential complications and relative and absolute contraindications. [2][3][4] To diminish those problems, bronchoscopically or ultrasonically guided PDT is suggested and airway control maintained with LMA during the PDT 5,6,8,10 . A short, bull neck without clear anatomical landmarks in morbidly obese patients presents a relative contraindication for PDT 3,4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to performing the procedure with the patient already positioned and the neck extended, we usually used ultrasound to identify the structures such as blood vessels close to the intended site of tracheostomy, the thyroid and cricoid cartilages, and the first three tracheal rings. Although the literature does not convincingly support using ultrasound routinely, but rather as an adjunct in selected patients, several studies and our personal experience have shown that ultrasound performed prior to percutaneous tracheostomy may be useful in avoiding injury to pretracheal vascular structures and in avoiding high placement of the tube 14,15 . Ultrasound examination performed before the procedure and fiberoptic bronchoscopy during the procedure can decrease complication rates and improve the safety of PDT 15 .…”
Section: T Klancir Et Almentioning
confidence: 95%
“…One must ensure adequate sedation and analgesia, preferably with a neuromuscular blockade using a short-acting intravenous paralytic agent in order to minimize coughing, biting and motion of the neck and trachea during the procedure. Although the literature does not convincingly support using ultrasound (US) routinely, but rather as an adjunct in selected patients, several studies have shown that ultrasound performed prior to PT may be useful in avoiding injury to pretracheal vascular structures and in avoiding high placement of the tube [24].…”
Section: Preventable Strategies Pre-procedural Preparationsmentioning
confidence: 99%